ACTIVITIES OF LAW ENFORCEMENT BODIES OF UKRAINE IN THE SPHERE OF ENSURING INFORMATION SECURITY - Lykhova, Sofiia; Sysoieva, Viktoriia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: determination of the main areas of activity of law enforcement agencies in ensuring the information security of the state, as well as analysis of regulatory consolidation and practical implementation of this activity. Methods: the research was conducted using a dialectical approach, methods of analysis, synthesis, as well as a number of general scientific and special legal research methods. Results: effective provision of information security by law enforcement agencies involves the search for new forms and methods of its provision, horizontal and vertical interaction at the domestic and international levels, legal analysis of the development of departmental regulations regulating this activity. Discussion: law enforcement agencies are obliged to counter threats to information security within their competence. Law enforcement agencies use a number of methods to implement information security powers. One of the main ones is the method of administrative and legal regulation. Ensuring information security remains a rather important task facing every state. One of the main subjects of its provision are law enforcement agencies, because they are called to protect society and the state from illegal encroachments, as well as maintain the state of legality, public safety and law and order. Unfortunately, the development of information technologies in modern society, in addition to positive innovations, also often creates negative consequences: new types of threats to information security arise; methods of concealing offenses committed in the information sphere are being improved; the amount of negative consequences from such offenses. Law enforcement agencies, whose main task can be formulated as ensuring legality in society, protecting the rights and interests of citizens, countering criminal and other offenses, cannot remain aloof from the problem of ensuring information security. However, the regulatory and legal consolidation of the directions of their activities in the field of ensuring information security contains certain features and also undergoes frequent changes.